Origins of Glutamatergic Terminals in the Inferior Colliculus Identified by Retrograde Transport and Expression of VGLUT1 and VGLUT2 Genes - Ito, Tetsufumi (Frontiers Research Foundation, 2010)
Terminals containing vesicular glutamate transporter (VGLUT) 2 make dense axosomatic synapses on tectothalamic GABAergic neurons. These are one of the three types of glutamatergic synapses in the inferior colliculus (IC) identified by one of three combinations of transporter protein: VGLUT1 only, VGLUT2 only, or both VGLUT1 and 2. To identify the source(s) of these three classes of glutamatergic terminals, we employed the injection of Fluorogold (FG) into the IC and retrograde transport in combination with in situ hybridization for VGLUT1 and VGLUT2 mRNA. The distribution of FG-positive soma was consistent with previous reports. In the auditory cortex, all FG-positive cells expressed only VGLUT1. In the IC, the majority of FG-positive cells expressed only VGLUT2. In the intermediate nucleus of the lateral lemniscus, most FG-positive cells expressed VGLUT2, and a few FG-positive cells expressed both VGLUT1 and 2. In the superior olivary complex (SOC), the majority of FG-positive cells expressing VGLUT2 were in the lateral superior olive, medial superior olive, and some periolivary nuclei. Fewer FG-positive cells expressed VGLUT1&2. In the ventral cochlear nucleus, almost all FG-positive cells expressed VGLUT1&2. On the other hand in the dorsal cochlear nucleus, the vast majority of FG-positive cells expressed only VGLUT2. Our data suggest that (1) the most likely sources of VGLUT2 terminals in the IC are the intermediate nucleus of the lateral lemniscus, the dorsal cochlear nucleus, the medial and lateral superior olive, and the IC itself, (2) VGLUT1 terminals in the IC originate only in the ipsilateral auditory cortex, and (3) VGLUT1&2 terminals in IC originate mainly from the VCN with minor contributions from the SOC and the lateral lemniscal nuclei.